Risk perception and factors associated With preferences for safe drinking water Outpatients at husm Kota bharu, kelantan - Azlan, Azlina (2012)
RISK PERSEPTION ON SAFE DRINKING WATER AND FACTORS ASSOCIATED WITH SAFE DRINKING WATER PREFERENCES AMONG HUSM OUTPATIENT CLINIC ATTENDEES IN KOTA BHARU KELANTAN. Safe drinking water source is the main topic discussed nowadays. Worldwide, food and water borne diseases resulted from consuming unsafe drinking water source. The aim of this study is to assess preference for safe drinking water, risk perception on safe drinking water and factors associated with preference for safe drinking water among Hospital University Sains Malaysia (HUSM) outpatient clinic attendees in Kota Bharu, Kelantan. A cross-sectional study was conducted on 115 outpatient clinic attendees at HUSM from 1st February to 30th April 2011. Convenient sampling was applied and face to face interview was conducted among consented respondents. The questionnaire used consistad of sociodemographic data, preference for drinking water, perception on drinking water quality and safe drinking water, preventive measures taken and general knowledge on water and health. The proportion of preference for safe drinking water among HUSM outpatient clinic attendees is low at 30.4% (95% CI: 0.22, 0.39) compared to preference of unsafe drinking water source which is 69.6% (95% CI: 0.61, 0.78). The health risk perception toward safe drinking water is almost equal between those who have high perceived health risks and those with low perceived health which are 46.1% (95% CI: 0.37, 0.55) and 53.9% (95% CI: 0.45, 0.63) consecutively. The significant associated factors for preference of safe drinking water are current used of drinking water source and monthly household income status. Person who currently uses municipal water supply as their drinking water source has 14.32 times odds to prefer safe than person who uses drinking water other sources of drinking water (95% CI: 4.08,50.30, p <0.001). Person with low monthly household income status has 4.38 times odds to prefer unsafe drinking water than person who is below poverty line (95 % CI: 1.18, 16.19, p = 0.027). Furthermore, person with middle household income status has 9.28 times odds for preference of unsafe drinking water source than person who is below poverty line (95 % CI: 2.12, 40.59, p - 0.003). The proportion of preference of safe drinking water among HUSM outpatient clinic attendees is low. Health risk perceptions toward safe drinking water are worrisome. Effective public awareness campaigns and interventions to improve health risk perception, to build stronger confidence toward municipal water sources will enable public to make good decision on safe drinking water. Therefore, these will help to reduce incidence of health risk related to water borne diseases.